The relationship between motivation and job performance among support staff at Majlis Perbandaran Hang Tuah Jaya, Melaka / Azrina Mohd Suhaimi...[et al] - Mohd Suhaimi, Azrina (Faculty of Business and Management, 2013)
Motivation is the key of a successful organization to maintain the continuity of the work in a powerful manner and help organizations to survive and also to find a need inside the employees. Motivate the staff leads them to broad skills which meet the organizational demands (Hala, 2009). According to Hala (2009), motivation drives the human beings to reach their goals and organization goals through every challenge and constraint they had been face in the workplace. Good performance depends on staff whether able to do things and willing to do things, which the level of performance depends on the level of motivation that stimulates someone to work and carry out the necessary tasks to achieve the goals (Hala, 2009). According to Harder (2008), there are varying or different set of factors influencing motivation. Basically, motivation is derived by several elelnents that can be measured to identify the level of motivation that each individual possess (Mohammed Abubakar & Abdullahi Yusuf, 2011).